Experimental Study on Self-Curing Concrete Using Sodium Polyacrylate - Harsh Sahu; Abhishek Diwakar; Kunal; Raghav; Prince Kumar; Ashish Juneja (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this study the effect of Sodium Polyacrylate as a self-curing-agent has been examined in order to optimizing the performance of concrete. Sodium Polyacrylate is used in different variations; 1%, 1.5%, and 2.0% of weight of cement, the test programme performed in this study, cement content; 1440 kg/m3, water-cement ratio; 0.4 were used. The physical properties of concrete were evaluated at different ages, up to 28 days. The concrete specimens are subjected to dry-air curing at room temperature during the experiment. Compressive strength test of concrete with agent and concrete without agent has been done on different days; 7, 14 and 28 days. The result shows that the use of self-curing agent in concrete effectively improves the physical properties compared with conventional concrete. It has been observed that 1% of Sodium Polyacrylate surpass the strength of conventional concrete. This agent shows drastic increase in strength (more than 25 N/mm2) for the M25 grade concrete. Higher cement content and/or lower water–cement ratio leads to more effective results of self-curing agents in concrete.
Keywords: Self-Curing; Sodium Polyacrylate